Posted by alex on Monday, March 7, 2011 at 8:17pm.
(1) x + 5y = -3
(2) 3x - 2y = 8
substitution method: we first choose one of the equation, and express one of the variables in terms of the other variable,, here let's choose equation (1), and express x in terms of y:
x + 5y = -3
x = -3 - 5y
now, we substitute this to equation (2), and we solve for y:
3x - 2y = 8
3(-3 - 5y) - 2y = 8
-9 - 15y -2y = 8
-17y = 17
y = -1
substituting this back to either equations to get x (let's choose (1)):
x = -3 - 5y
x = -3 -5(-1)
x = -3 + 5
x = 2
hope this helps~ :)
Math- Adv. Alg. w/ Trig. - I need help simplifying this expression: (3x^3y^5 + ...
math - linerar equactions 5x-2y=4 3x+y=9 3x-5y=13 x-2y=5
algebra - how do I do this Solve for x. 3x 2y = 6 Add 2y to both sides ...
Alegbra - I need help with this problem 0.3x-0.2y=4 0.5x+0.5y=45/23 3x-2y=40 5x+...
Limit Calculas - Evaluate lim->4 sin(2y)/tan(5y) Here is what I have so ...
Algebra (check answers) - Could you please check my answers we are using ...
Algebra - What is the answer to 7x+2y=16 and -21x-6y=24 using the substituion ...
calculus - Evaluate lim->4 sin(2y)/tan(5y) Here is what I have so far. I ...
Algebra 2 - Solve the system using any algebraic method. 22.)2x-5y=4 23.)5x+7y=...
Math please help asap - Solve using elimination.......answers must be in ordered...
For Further Reading